Enfoque económico de la empresa “Mascaro S.A.” mediante la aplicación de los indicies financieros 2018-2019. - Castillo Coronel, Andrea Vanessa (My University, 2020)
The development of the business sectors and the global economy consider the capacity of the human being as the main point for the generation of transformations based on new ideas; Likewise, there is a need to improve the information systems in the financial-accounting technical processes and the efficiency in their application, in this way it will be possible to transform the knowledge based on the technological support. The level of development acquired by humanity demonstrates that institutions must go hand in hand with technological changes in order not to be left behind in their forms of production, in their financial, administrative and accounting processes, that is, to rehabilitate their productive management and Establish the key procedures. The research focuses on the analysis and interpretation of the financial statements of MASCARO S.A. from the city of Machala, corresponding to the 2018 - 2019 periods, for this purpose, the objectives were “To carry out an economic approach through financial indicators of solvency, liquidity and profitability of the company“ Mascaro S.A. ” to determine the problems that affect its growth and development, based on which policies will be established to improve business management ”and“ Evaluate through financial indicators the behavior of the company “Mascaro S.A.” During the period 2018-2019 and determine the fulfillment of the planned objectives ”, for this the financial statements of the company“ Mascaro SA ”were used, and the vertical, horizontal and financial indicators analytical methods, after the financial analysis of the company “Mascaro SA” It was possible to establish the following conclusions, the cost of sales of the company is very high, this increased more in 2019, from 66% to 72%, thus decreasing the profits of the company; administration and sales expenses are also higher during the year 2019, it doubled, all this is reflected at the end of the 2019 fiscal year, in which profits are negative by -0.2%. Document accounts and accounts receivable from unrelated customers, other related accounts receivable, and the provision of bad accounts keep the company even with accounts receivable problems, which hinder its financial performance. Obligations with financial institutions have increased current liabilities by 24% compared to 2018. The company's net worth increased by 6%. The financial conditions of the company were better during 2018, this is reflected in the main indicators such as solvency, acid test, working capital and profit margin, so it is recommended to carefully monitor costs of sale and accounts payable in relation to solvency, there must be a relationship between the amount of the liability and the equity of the company, in addition to this, it is also recommended the establishment of appropriate credit policies, consistent strategies that allow controlling your accounts receivable, reduce the risk of bad debts; Likewise, accounts payable must be managed efficiently, thus avoiding unnecessary debts.
El desarrollo de los sectores empresariales y de la economía global consideran la capacidad del ser humano como punto primordial para la generación de transformaciones partiendo de nuevas ideas; así mismo, existe la necesidad de mejorar los sistemas de información en los procesos técnicos financieros – contables y la eficiencia en su aplicación, de esta manera se logrará transformar el conocimiento en base al soporte tecnológico. El nivel de desarrollo adquirido por la humanidad demuestra que las instituciones deben ir a la par de los cambios tecnológicos a fin de no quedarse atrás en sus formas de producción, en sus procesos financieros, administrativos y contables, es decir, rehabilitar sus gestiones productivas y establecer los procedimientos claves. La investigación se centra en el análisis e interpretación de los Estados financieros de la empresa MASCARO S.A. de la ciudad de Machala, correspondiente a los periodos 2018 – 2019, para esto se planteó como objetivos “Realizar un enfoque económico por medio de indicadores financieros de solvencia, liquidez y rentabilidad de la empresa “Mascaro S.A.” para determinar los problemas que afectan su crecimiento y desarrollo, en base a los cuales se establecerá políticas que permitan mejorar la gestión empresarial” y “Evaluar por medio de indicadores financieros el comportamiento de la empresa “Mascaro S.A.” durante el período 2018 -2019 y determinar el cumplimiento de los objetivos previstos”, para esto se utilizó los estados financieros de la empresa “Mascaro S.A.”, y los métodos analíticos vertical, horizontal e indicadores financieros, ddespués de realizado el análisis financiero de la empresa “Mascaro S.A.” fue posible establecer las siguientes conclusiones, el costo de ventas de la empresa es muy alto, este se incrementó más en el año 2019, del 66% al 72%, disminuyendo por ende las utilidades de la empresa; también los gastos de administración y ventas son superiores durante el año 2019, se duplicó, todo esto se refleja al final del ejercicio 2019, en el cual las utilidades son negativas en -0,2%. Las cuentas de documentos y cuentas por cobrar clientes no relacionados, otras cuentas por cobrar relacionadas, y la provisión cuentas incobrables mantienen a la empresa aun con problemas de cuentas por cobrar, las cuales dificultan su desempeño financiero. Las obligaciones con instituciones financieras han incrementado el pasivo corriente un 24% en relación al 2018. El patrimonio neto de la empresa se incrementó en 6%. Las condiciones financieras de la empresa fueron mejores durante el año 2018, esto se refleja en los principales indicadores como son la solvencia, la prueba ácida, el capital de trabajo y el margen de utilidad, por lo cual se recomienda vigilar con mucho cuidado los costos de venta y las cuentas por pagar en relación a la solvencia, debe existir una relación entre el monto del pasivo y el capital contable de la empresa, además de esto, también se recomienda el establecimiento de políticas de crédito adecuadas, estrategias acordes que permitan controlar sus cuentas por cobrar, disminuir el riesgo de incobrabilidad; así mismo, las cuentas por pagar deben ser manejadas de manera eficiente, evitando así deudas innecesarias.
Keywords: ESTADOS FINANCIEROS; SOLVENCIA; LIQUIDEZ; PASIVO